2011
DOI: 10.1007/s12098-011-0470-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pediatric Scrub Typhus during an Outbreak in the North Eastern Region of India: Peculiarities in Clinical Presentation, Laboratory Findings and Complications

Abstract: This is the first outbreak report from the north eastern region of India with varied clinical presentations, laboratory investigations and complications. Weil Felix test still remains fruitful for diagnosing this disease in a resource limited set up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 12 publications
11
86
6
Order By: Relevance
“…Rickettsial diseases have been reported from the various parts of India and are showing a trend of re-emergence [1][2][3][4][5][6][7][8][9]. More than 75% of our cases occurred during the fourth and fifth year of our five-year analysis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Rickettsial diseases have been reported from the various parts of India and are showing a trend of re-emergence [1][2][3][4][5][6][7][8][9]. More than 75% of our cases occurred during the fourth and fifth year of our five-year analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Rickettsial disease has been reported from various parts of India, such as Tamil Nadu, Karnataka, Kerala, Maharashtra, and some parts of northern India [1][2][3][4][5][6][7][8][9]. The infection has established itself as an endemic disease in Southeast Asia including Thailand, China, and Taiwan [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Dass R et al reported seizures in 12.5 % of cases and altered sensorium in 16.6 % of cases. In their study, meningoencephalitis was seen in 29.2% of untreated cases of which 2 patients with low GCS were ventilated for 4 days each (9) , Palanivel et al (5) reported altered sensorium in 58% of cases.…”
Section: Study Hepatomegaly Lymphadenopathy Escharmentioning
confidence: 85%
“…All other causes of fever were ruled out. Palanivel et al (5) , Inamdar et al (6) , Udayan U et al (3) , Dass R et al (9) also found fever in all children.…”
Section: Clinical Featuresmentioning
confidence: 92%
“…Over one-third of patients with scrub typhus present with gastrointestinal symptoms. 3,4 Primary intra-abdominal processes leading to secondary peritonitis are numerous, including diseases or injuries of the gastrointestinal or genitourinary tracts. 5 Peritonitis in patients with scrub typhus has never been reported.…”
mentioning
confidence: 99%